Company To Be Acquired by Sierra Atlantic - Kumar Shah, Amit (2010)
This internship basically helps Sierra Atlantic to achieve its goal for the identification of suitable candidates in UK which can be acquired by the company to grow inorganically and expand its business further in UK.